Use of high resolution/accurate mass full scan/data-dependent acquisition for targeted/non-targeted screening in equine doping control. Issue 13 (12th March 2021) - You, Youwen; Proctor, Rachel M.; Guo, Kevin; Li, Xiaoqing; Xue, Evan; Guan, Fuyu; Robinson, Mary A.
Abstract : A targeted/non-targeted LC-HRMS/MS method for equine doping screening analysis was developed using a QE-Plus Orbitrap mass spectrometer combined with an in-house built compound database and spectral library. Abstract : High-resolution mass spectrometry (HRMS) is a very powerful technology for equine doping control analysis. The more recently developed hybrid type of Orbitrap-based HRMS instrument allows for both targeted and non-targeted screening analyses in a single liquid chromatography-high resolution tandem mass spectrometry (LC-HRMS/MS) run. In the present study, an LC-HRMS/MS method was developed and validated to detect prohibited substances in equine sports. The substances were recovered from equine plasma by liquid–liquid extraction (LLE) using methyl tert -butyl ether and were separated on a C18 reversed-phase column using mobile phases of 5 mM ammonium formate and acetonitrile. A 7.5 min LC gradient was employed to elute substances and results indicated that the LC method generated sharp and symmetric chromatographic peaks. An in-house equine doping compound database and a spectral library were built to increase method specificity for substances of interest. Five criteria, i.e. accurate mass, retention time, isotope pattern, selected HRMS/MS fragment ions (compound database) and HRMS/MS spectra (spectral library), were employed for targeted screening. We utilized these criteria to validate targeted detection of 451 substances within our in-house equine doping compound database. By using all five criteria in screening, the false screening positive rate is significantly reduced. A screening strategy and a Microsoft Excel macro were developed to facilitate interpretation and reporting of results. As the simultaneous acquisition of the full scan HRMS data provides the opportunity for retrospective non-targeted analysis, our findings highlight the use of this novel methodology as a simple, rapid, and reliably reproducible strategy to meet the challenge of identifying an increasing number of doping substances that could potentially impact the integrity of the horse racing community.